The Immunological Effectiveness of Some Common Plants (Baghdad Science Journal, 2014)
Three plant species were picked randomly and their alcoholic extracts have been screened to know their effects on the phagocytic capability and intracellular killing of yeast by human peripheral macrophages. Macrophage cultures were incubated with different concentration of each plant extract: for 15 min., 30 min .and 45 min. The phagocytes activity in Iresine herbstii extract was significantly (p?0.05) increased with increasing dose and time of incubation. In Mentha piperita extract, increasing in dose and time of incubation leads to elevate phagocytic capbility, especially in the dose of 20% and 25% of plant extract, perhaps because the antimicrobial and antiviral activities of this plant, as well as strong antioxidant and antitumor actions. While in Elettaria cardamomum, a significant elevation has been observed in phagocytic efficiency when the dose of extract increase to 15%, then decreased in the subsequent doses (20% and 25%), in three periods of time. These findings may suggest that cardamom exert immunomodulatory roles.